The Effect of Financial Crisis and Macroeconomic Factors on FDI in Developing Countries - Hasli, Anita; Ibrahim, Nurhani Aba; Ho, Catherine S.F. (International Journal of Economics and Financial Issues, 2017)
Developing countries needs FDI to be at par with the progress of developed countries. The dearth of study on the effects of financial crisis on FDI justifies the objective which is to examine the potential effect of financial crisis inclusive of macroeconomic factors as control variables on FDI in dataset 23 developing countries for the period 1993-2013. This study includes descriptive analysis, correlation test, stationary test and regression analysis. The random effects generalized least square (GLS) estimator is used in the regression to examine the potential effect of financial crisis and macroeconomic factors on the inflow of FDI. Foremost, the US financial crisis has a positive significance to the inflow of FDI which validates Krugman’s theory on fire-sale FDI. However, country specific economic recession, lending rates and natural resources discourage inflow of FDI. Nonetheless, trade openness, domestic currency, money supply and domestic fixed investment encourage FDI in developing countries. Keywords: Foreign Direct Investment; financial crisis; REM; developing countries JEL Classifications: C33; F21; G01; P52